Resolution of Gastroesophageal Reflux Disease Following Correction for Upper Cross Syndrome—A Case Study and Brief Review - Eric Chun-Pu Chu; Kenneth R. Butler (Clinics and Practice, 2021)
Upper cross syndrome (UCS) is a condition caused from prolonged poor posture manifesting as thoracic hyperkyphosis with forward head and shoulder postures. It has been associated with several other secondary conditions, causing pain and discomfort to those with the condition. This is a case report of a 35-year-old female presenting to clinic with a sharp pain in the neck, upper back, and sternum area for 4 weeks and gastroesophageal reflux disease (GERD). She had been working at home for several months after the shelter at home order was issued. Following evaluation and corrective treatment with cervical adjustment and soft tissue massage, the patient’s posture improved and reported full pain resolution. Her symptoms of GERD concurrently resolved as well. She continued to receive chiropractic adjustment two times per month for correcting spinal misalignment. Full restoration of posture was attained on the full spine radiographs at 9 months follow-up. The patient remained symptom-free at 12 months follow-up. Manipulative and preventive therapies aimed at treating and preventing UCS should be more widely adopted to prevent secondary conditions.